Design of portable rheometer with new vane geometry to estimate concrete rheological parameters - Soualhi, Hamza; Kadri, El-Hadj; Ngo, Tien-Tung; Bouvet, Adrien; Cussigh, François; Tahar, Zine-El-Abidine (Journal of Civil Engineering and Management, 2017)
This paper presents the development of a portable vane rheometer to estimate concrete plastic viscosity and yield stress. The apparatus can be used not only in laboratory but also on construction site. In this study, new blade geometry was proposed to minimize the effect of segregation of concrete during testing, and also to expand the wide range of concrete workability with a slump of approximately from 7 cm to fluid concrete, and concrete with high plastic viscosity such as concrete with mineral additions. The used blade (U shaped and reversed) allows reducing the vibration of the apparatus, and obtaining more stable measurements. The obtained results permit validating the rheometer test procedure and confirmed that the results are reliable, with a low coefficient of variation of 9% for repetitive test and of 5.8% for reproductive tests. First published online: 23 Jun 2016